Quality of Islamic education management in developing curriculums of industrial era 4.0 - Chusnunia, Subandi, Suhono, Ahmad Fauzan, Agus Jatmiko, (Opción, 2019)
The aim of the study is to investigate the quality of Islamic education management in developing curriculums of industrial era 4.0. This research was a qualitative approach, which is describing phenomena in the open, through data collection tools, namely interviews, observation and documentation. As a result, Total quality management (TQM) is an effort to create a quality culture that encourages all members of his staff to satisfy customers. In conclusion, Islamic universities are able to serve customers (customer’s satisfaction) and to be choices in the hearts of the people.